(untitled) (TAJ: Journal of Teachers Association, 2018)
Objective: To review the management and outcome of postoperative complications after common obstetric and gynecologic surgeries performed in outside nonacademic private hospitals (clinics) and peripheral public hospitals (districts hospitals) and later admitted in Department of Obstetrics and Gynecology of Rajshahi Medical College Hospital (RMCH). RMCH is a tertiary referral hospital where all complicated patients were referred for better management from surrounding hospital. Methodology: This Quasi-experimental study was carried out in the Department of Obstetrics and Gynecology at Rajshahi Medical College Hospital, Rajshahi, Bangladesh between July 1, 2015 and June 30, 2017. All patients admitted with post operative complications following common obstetric and gynecologic surgeries during this period were included. Patients admitted with post operative complications, where primary surgery was done in this hospital were excluded. The common obstetric and gynaecological surgeries were caesarean sections (LUCS), total abdominal hysterectomy (TAH) and vaginal hysterectomy (VH) performed outside Rajshahi Medical College Hospital. Result: During this period a total of 39,929 patients were admitted through emergency way in obstetrics and gynecology department of Rajshahi Medical College Hospital. Among them 675 patients were admitted with the complaints of post operative complications following common obstetric and gynecologic surgeries with rate being 1.7%. In 560(83%) cases surgery was done in clinics and 115(17%) cases surgery was done in district hospitals. Among the patients 580(85.9%) cases primary operation was done by non-gynaecologic surgeon and 95(14.1%) cases by gynaecologic surgeon. Caesarean section was the primary obstetric surgery in 405(60%) cases .Gynecologic surgeries included TAH in 185(27.4%) cases and VH in 85(12.6%) cases. We found 25(3.7%) patients died from these complications. Repeat surgery was done in 90(13.33%) cases. Genitourinary fistula repair was done in 41 cases (45.55%). Rests were improved by conservative management. Conclusion: Any surgical procedure carries risk of complications. Careful selection of patients with suitable indications for operations, expertise of the surgeon, good surgical technique, proper knowledge of pelvic anatomy and careful postoperative follow up can minimize recognized complications. TAJ 2017; 30(2): 7-12